Growth rate of German economy normalizing after prolonged economic boom - Claus Michelsen; Christian Breuer; Martin Bruns; Max Hanisch; Simon Junker; Thore Schlaak (DIW Weekly Report, 2018)
The German economy continues to perform well although the boom has ended. However, at 1.5 percent, German GDP will increase this year at a lower rate than expected at the beginning of the year. Nevertheless, concerns about an imminent recession should give way to the assessment that the pace of the German economy is normalizing after years of above-average growth due to robust foreign demand and increasing employment levels. A gradual reduction in high capacity utilization will be accompanied by lower GDP growth; in the short term, however, this will be overshadowed by catch-up effects in the automotive industry following production and delivery problems and by the fiscal income boosts at the beginning of 2019, the most important being reduced social security contributions.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook